2013
DOI: 10.1007/s11051-013-2082-7
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized NaA nanozeolites labeled with 224,225Ra for targeted alpha therapy

Abstract: The 223Ra, 224Ra, and 225Ra radioisotopes exhibit very attractive nuclear properties for application in radionuclide therapy. Unfortunately the lack of appropriate bifunctional ligand for radium is the reason why these radionuclides have not found application in receptor-targeted therapy. In the present work, the potential usefulness of the NaA nanozeolite as a carrier for radium radionuclides has been studied. 224Ra and 225Ra, α-particle emitting radionuclides, have been absorbed in the nanometer-sized NaA ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 29 publications
3
66
0
Order By: Relevance
“…The in vivo generators 223 Ra, 224 Ra, and 225 Ra are also promising candidates for TAT [16][17][18][19][20][21][22]. Similar to 225 Ac, during the decay of 223 Ra and 225 Ra, ~28 MeV of energy is released and ~90-94% of this energy is associated with four sequentially emitted α-particles ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo generators 223 Ra, 224 Ra, and 225 Ra are also promising candidates for TAT [16][17][18][19][20][21][22]. Similar to 225 Ac, during the decay of 223 Ra and 225 Ra, ~28 MeV of energy is released and ~90-94% of this energy is associated with four sequentially emitted α-particles ( Fig.…”
mentioning
confidence: 99%
“…Investigations of the potential usefulness of liposomes with a diameter of ~120 nm showed retention of 223 Ra up to 93% after 4.2 d in serum [16,17]. Also, recent work on the use of the NaA nanozeolite particles of ~100 nm to carry Ra radionuclides has been reported [19].…”
mentioning
confidence: 99%
“…So, the zeolite nanostructures with different selectivities can act as the ion-exchanger. Piotrowska et al 94 proposed the use of nanozeolite whose channels and cavities were filled with cations of 224 Ra and 225 Ra by means of simple ion exchange without any additional operations. The 223 Ra, 224 Ra, and 225 Ra radioisotopes exhibit very attractive nuclear properties for application in radionuclide therapy.…”
Section: D Nanocarriersmentioning
confidence: 99%
“…Unfortunately, the lack of appropriate bifunctional ligands for radium is the reason why these radionuclides have not found application in receptor-targeted therapy. 94 These α-particle emitting radionuclides were absorbed in the nanometer-sized NaA zeolite (30-70 nm) through simple ion exchange. 224 Ra and 225 Ra radiolabeled nanozeolites exhibited very high stability in human serum.…”
Section: D Nanocarriersmentioning
confidence: 99%
“…Daughter retention (up to 88%) increased with additional gadolinium phosphate shells. Interestingly, Piotrowska et al (102) found that the first daughter of 225 Ac, 221 Fr, was well retained by biocompatible crystalline aluminosilicate nanozeolites (40 to 120 nm in diameter) when radiolabeled with 225 Ra. These constructs also stably retained 225 Ac in the presence of ethylene-diaminetetraacetic acid (≤5.5 ± 2.5% release) and in human blood serum (≤2.3 ± 1.9%).…”
Section: Preclinical α-Particle Therapy Delivered By Nanometer-sizmentioning
confidence: 99%